Mediating institutional quality on transformational leadership and corporate performance of nigeria national petroleum corporation (NNPC) - Osuagwu, Justine U.; Hassan, Mazlan; Akpan, Sunday S. (2018)
Performance of NNPC has been observed to be abysmally below expectations and there are growing concernson possible cause of this poor performance. One area that often comes to debates is the leadership of the corporation. But other factors that are institutionally related have also been found to affect the way an organization performed. This research thus examines the effect of transformational leadership( T F L ) on corporate performance with institutional quality as a mediator. A survey research design was employed to collect data from 261 respondents from NNPC and it affiliations and analyzed using partial least squares structural equation modeling.The study revealed that T F L had a significant positive effect on performance of NNPC while institutional quality did not mediate the relationship betweenT F Land corporate performance;rather, it had a significant negative effect on performance of NNPC.Therefore,T F L a n d institution quality each can independently cause significant change in performance of NNPC .The study recommends the adoption of T F L while institutional quality should be improved to achieve the desired performance of NNPC is expected in Nigeria.